Analisis Karakter Mandiri pada Mata Pelajaran Ekonomi di Madrasah Aliyah Nurul Hidayah Bantan Kab. Bengkalis - Ummi Mawaddah Alfitri (Jurnal Syntax Transformation, 2021)
This research aimed at knowing student independent character on Economics subject at Islamic Senior High School of Nurul Hidayah Bantan. It was instigated by there are student who delay the completion of duty trapping the deadline ginen the teacher’s time, A student who doesn’t confedent in the result of works, there are students who are unable to do the task of the objective given by teacher, there are a fear of students who are facing risk of the choices that have taken, the fear is afraid to fail, and there are many less capable student solving problem of his own problems, which he defaced during the teaching process of teaching. This research was qualitative. The subjects of this research were the tenth-grade students of Social Science that were 61 students, and 2 Economics subject teachers who were directly as the informants. The object was student independent character. The technique of data were Questionnaire, interview, and documentation. The technique of data analysis was used descriptive qualitative analysis with percentage. Based on the data analysis showed that an student independent character on Economics subject at Islamic Senior High School of Nurul Hidayah Bantan overall was on good category with 63,29% percentage. This percentage was categorized in the range of 61%-80%.